Evaluation Of The Effectiveness Of Digital-Based Public Services In Makassar City - Jumalia Mannayong (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to evaluate the effectiveness of digital-based public service programs in Makassar City. The main focus of the research is to analyze the extent to which the implementation of digital technology in public services can enhance operational efficiency and public satisfaction. The research methods used are quantitative surveys and qualitative interviews with stakeholders, including government employees and city residents who use these digital services. Data analysis is conducted to measure the performance of digital services, identify obstacles faced in implementation, and assess the impact on citizen satisfaction. The findings indicate that the use of digital technology in public services significantly improves administrative efficiency and process transparency. However, several challenges need to be addressed, such as technical difficulties, resistance to change, and the lack of digital literacy among the population. Based on these findings, the study provides strategic recommendations to improve the implementation of digital public services to achieve higher satisfaction among Makassar City residents.